The Lamination of Infinitely Renormalizable Dissipative Gap Maps: Analyticity, Holonomies and Conjugacies - Gouveia, Márcio Ricardo Alves [UNESP]; Colli, Eduardo (Springer Nature, 2012)
Motivated by return maps near saddles for three-dimensional flows and also by return maps in the torus associated to Cherry flows, we study gap maps with derivative positive and smaller than one outside the discontinuity point. We prove that the lamination of infinitely renormalizable maps (or else maps with irrational rotation numbers) has analytic leaves in a natural subset of a Banach space of analytic maps of this kind. With maps having Hölder continuous derivative and derivative bounded away from zero, we also prove Hölder continuity of holonomies of the lamination and also of conjugacies between maps having the same combinatorics. © 2011 Springer Basel AG.
Keywords: Cherry flow; Cherry map; Conjugacy; Flows on surfaces; Gap map; Holonomy map; Irrational rotation number; Lorenz map; Renormalization